INCIDENCE DE LA REFORME FISCALE SUR LA MOBILISATION DES RECETTES PUBLIQUES - Oseyatoko, Marcel; FATAKI N’GBALE, Jacques Richard (IJRDO - Journal of Business Management, 2018)
In what concerns us, our major concern would be to seek to know the incidence or the impact of this tax reform in the mobilization of the receipts of the Treasury generated, case of the value-added tax (VAT) in the center of synthetic taxes of Isiro in connection with the retrocessions.¶The anticipated result of this research proves that the transfer of the VAT collected on behalf of the Treasury is carried out only in Kisangani or Kinshasa whereas an Agency of the Central Bank of Congo is established in Isiro. ¶This situation disadvantages the Center of the Synthetic Taxes (CIS) of Isiro as regards retrocession to the sight of the perceptions operated in the entity, that is to say a loss of earnings for the entity.¶